Teaching English For Young Learners - Ida Prayatni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2019)
Abstract : Language as a means of communication plays very important role in social relationship among human beings. The English language is the first foreign language we teach to children at very early stages of schooling. The primary aim of teaching English in the early years of schooling is to motivate young learners to be ready and have self-confident in learning English at higher levels of education. Some children are born to parents who are polyglots, so they have to acquire two or three different languages. Some others learn second or third language because they have to immigrate to a new country. Others learn English as foreign language because English is not their native language in their country. Teaching English to young learners then can be beneficial or detrimental to learners. It will be beneficial if the teachers can facilitate learning and enable learners to bring to language learning their curiosity and eagerness to make sense of the world, as a result, the teachers may help the learners are able to overcome their problem even the most demanding tasks with enthusiasm and willingness.Keywords : Teaching English, English for young learners